2007
DOI: 10.1074/jbc.m609347200
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin Potentiates the Activation of Procaspase-3 by Accelerating Its Proteolytic Maturation

Abstract: We have previously shown that procaspase-3 exists in a high molecular weight complex in neonatal rat brain. Here, we purify and identify the protein that interacts with procaspase-3 from rat neonatal cortex. We searched binding proteins to procaspase-3 from a cytosolic extract of neonatal rat brain using chromatogram, two-dimensional gel electrophoresis, and far Apoptosis is a type of cell death resulting from the activation of a genetically regulated cell suicide program. In the nematode Caenorhabditis elegan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…However, in recent years, it has been shown that the CnB is not just a simple protein as the regulatory subunit of CnA. Cytosolic CnB can interact with tubulin, heat shock protein 60 (13), procaspase-3 (14), and PSMA7 (15) and therefore plays very important role in apoptosis and the proteasome pathway, which are not dependent on the phosphatase activity of CnA. In previous work, we found that i.p.…”
mentioning
confidence: 83%
“…However, in recent years, it has been shown that the CnB is not just a simple protein as the regulatory subunit of CnA. Cytosolic CnB can interact with tubulin, heat shock protein 60 (13), procaspase-3 (14), and PSMA7 (15) and therefore plays very important role in apoptosis and the proteasome pathway, which are not dependent on the phosphatase activity of CnA. In previous work, we found that i.p.…”
mentioning
confidence: 83%
“…Total protein was mixed with Laemmli buffer, separated by SDS-PAGE and transferred to PVDF membranes (Millipore Corporation). Immunoblotting and immunoprecipitaion were carried out as described previously [24], [25]. Briefly, equal protein concentrations of lysates were incubated with antibody for 16 h, followed by incubation with Protein G Sepharose (Amersham Biosciences) for 1 h. The Sepharose beads were washed five times with the buffer described above, associated proteins were recovered by boiling in Laemmli buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Dephosphorylation of caspase-3 at Ser150 site by PP2A increased caspase-3 activity, which was essential to trigger apoptosis in neutrophils (3). In addition, it has been shown that PP2B interacted with procaspase-3 and promoted caspase-3 maturation (100). On the other hand, protein phosphatases can be cleaved and regulated by caspases (66).…”
Section: Stps Mediated Regulation On Apoptosis Executioner Machinerymentioning
confidence: 99%